Perancangan Sistem Persediaan Berbasis Website pada PT. Asahi Fibreglass - Ignatius Adrian Mastan; Raynaldo Kurniawan (Universitas Bunda Mulia, 2020)
The development of technology which continues to increase rapidly has an impact on the internal processing of a company that is required to run faster. Information system technology is the main solution as a tool for activities in a company that is faster and more practical, and allows obtaining data that is more valid, precise and minimizes errors. PT Asahi Fibreglass is a company in Jakarta which started its business from 2001 which is engaged in manufacturing and marketing products for the needs of fiberglass products for industrial, residential, building and property needs. In operational activities of PT. Asahi Fibreglass has several obstacles in the process of recording stock items which still use a book-based recording method which makes recording look messy, there are differences in recording the physical stock of goods in the warehouse with the recording of goods recorded in a Microsoft Excel file, there are missing or tucked data because it still uses manual methods and is still book-based. The purpose of creating a web-based inventory information system at PT Asahi Fibreglass is a system improvement in regulating the flow or path of the process of in and out of warehouse goods that will replace the old inventory system that still uses Microsoft Excel, as well as speed up the process of making reports, and minimize errors in the inventory recording process.